Analisis Desain Struktur IPLT Kota Pagar Alam - Ali Okta Akbar; M.Sang Gumilar; Tarmizi Tarmizi (JURNAL ILMIAH BERING'S, 2017)
Building Analysis of IPLT in Padang Karet, Pagar Alam City have ponds, consist of Solid Saparation Chamber (SSC), anaerobic I, anaerobic II, facultative and maturation. SSC building structures include steel roof buildings, steel columns, short columns, cast walls and floor plates. Analysis of steel roofs, steel columns and short columns using SAAP 2000 programming while for studio plates, replace stiffener. Anaerobic columns I, anaerobic II, facultative ponds, ponds and maturation ponds are manually counted. Analysis of the research is done to determine the structure and cost to be used. Costs used in analysis with the Ms.Excel program. The parameters used in the analysis use fc '= 25 MPa, fy = 400 MPa, K-225 concrete and u-34 steel. Combination using SNI 03-1729-2002. Based on the analysis performed, pipe (6 ') is note safe so that pipe (10') are used. Budget plan costs more economically using the pipe (6 ').